Whose Risks and Benefits?. Issue 4 (July 2015) - Kaebnick, Gregory E.
Abstract This issue of the Report, like many others, was assembled with an eye more to diversity of topics and themes than to commonality. But as also often happens, some topics and themes arise anyway. Two pieces in this issue discuss the disclosure of information that's uncovered in the course of genetic testing and try to develop some guidance for physicians and researchers. A third offers an historical look at changing practices.